Markers of heart failure with preserved ejection fraction in patients with unexplained dyspnea - A. A. Ivanova; E. A. Rogozhkina; Yu. S. Timofeev; O. N. Dzhioeva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To evaluate the prevalence of clinical, history, laboratory and ultrasound markers of heart failure with preserved ejection fraction (HFpEF) in patients with unexplained dyspnea, as well as to identify markers of structural myocardial remodeling in this group of patients.Material and methods. This retrospective study included 504 patients aged 18 to 84 years who were hospitalized from July 1, 2022 to March 31, 2023. Patients were divided into two groups depending on the presence of dyspnea. A comparative analysis of ultrasound parameters was carried out in order to identify myocardial structural remodeling.Results. A number of associated conditions and metabolic disorders, which are known to be risk factors for HFpEF, were detected more often in patients with unexplained dyspnea and myocardial remodeling. A model to determine the probability of structural remodeling was developed. Two most significant indicators were dyspnea and diabetes.Conclusion. This study demonstrated the relationship between unexplained dyspnea and structural myocardial remodeling. Identification of certain clinical and morphological signs of HFpEF in such patients requires apprehensive attitude and in-depth examination in order to rule out it.